دور تقانات المعلومات الحديثة في تحسين جودة الخدمة المصرفية : دراسة استطلاعية لآراء عينة من العاملين في بعض فروع مصرفي الرشيد و الرافدين في مدينة الموصل - د. نبال يونس محمد (PROSPECTIVE RESEARCHES, 2023)
The search attempts to define the role of modern information technology in the modern quality of banking service, as was poor awareness of the banking and financial issues among workers in the departments of banks and the low volume of activities and events carried out by banks, particularly those which are related to information technology. The research presumes initially that all these constraints are resulting from banks not adopting information technology to ensure the provision of services consistent with customer needs and desires. The research tries to find the answer to the following questions. 1. Is there a discrepancy between the banks researched by adopting information technology in banking operations? 2. Is there a discrepancy between the banks discussed in the quality of service provided by the bank? 3. What is the nature and impact of correlation between information technology and the quality of banking service? To answer these questions, the researcher depended on four hypotheses which show the contrast between major banks discussed in the research and the relationship and influence between them and to test the validity of these assumptions, data has been collected by means of a questionnaire prepared for this purpose. The data were analyzed using a set of statistical methods.